Introducción al uso de QALYs y EQ-5D en la evaluación de tecnologías en Colombia (2011)
The Quality-Adjusted Life Year (QALY) is a measurement to quantify the effect of a specific sanitary intervention on mortality and morbidity. EuroQol 5D (EQ5D) is a measurement instrument for QALYs. This article presents an introduction for its use in assessing health technologies in Colombia.